2020
DOI: 10.21608/jram.2020.33184.1064
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin Converting Enzyme Gene Polymorphism in Dyslipidemia and Hypertension

Abstract: Background: Hypertension and dyslipidemia have a multifactorial background based on genetic and environmental interactive factors. Increasing blood pressure (BP) and hypertension incidence have also been found to be linked with elevated blood lipids rates. Insertion/deletion (I/D) polymorphisms of the angiotensin converting enzyme (ACE) are said to be linked to pathogenesis of both hypertension and dyslipidemia.Objectives: to investigate the presence of the three genotypes of ACE gene (I/D) polymorphisms with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…26 We also analyzed a number of conventional cardiovascular risk variables in patients with IHD and found that HTN and dyslipidemia significantly influence the occurrence of IHD. These findings agreed with research conducted in Pakistan, 23 Egypt, 27 and Iran. 28 Hypertension and dyslipidemia contribute to IHD through a number of different mechanisms.…”
Section: Discussionsupporting
confidence: 92%
“…26 We also analyzed a number of conventional cardiovascular risk variables in patients with IHD and found that HTN and dyslipidemia significantly influence the occurrence of IHD. These findings agreed with research conducted in Pakistan, 23 Egypt, 27 and Iran. 28 Hypertension and dyslipidemia contribute to IHD through a number of different mechanisms.…”
Section: Discussionsupporting
confidence: 92%